Examining Alternative Attractiveness Effects on Brand Trust-Loyalty Relationship in Samsung Users - Prabawa, Dewa Made Surya; Handrito, Radityo Putro (Jurnal Manajemen Pemasaran dan Perilaku Konsumen, 2025)
Purpose – This study aims to examine the effect of customer satisfaction on the loyalty of Samsung smartphone users in Indonesia, with brand trust as a mediating variable and alternative attractiveness as a moderating variable.    Design/methodology/approach – This study employs an explanatory research design to investigate the causal relationships among customer satisfaction, brand trust, alternative attractiveness, and customer loyalty. Using a purposive sampling technique, data were collected from 321 Samsung smartphone users aged at least 17 years. The proposed research model was analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0 to evaluate the direct, indirect, and moderating effects.   Findings – The results indicate that customer satisfaction has a positive and significant direct effect on both brand trust and customer loyalty. Brand trust also has a positive and significant effect on customer loyalty and mediates the relationship between customer satisfaction and loyalty. However, alternative attractiveness does not significantly moderate the relationship between brand trust and customer loyalty. These findings suggest that satisfied customers who develop strong trust in the Samsung brand tend to remain loyal despite the availability of competing smartphone brands.   Originality/value – This study contributes to the customer loyalty literature by integrating mediation and moderation mechanisms to explain loyalty formation in the smartphone industry. It highlights the mediating role of brand trust and demonstrates that alternative attractiveness does not weaken the relationship between brand trust and loyalty, providing practical insights for smartphone manufacturers seeking to strengthen long-term customer retention.